2018
DOI: 10.1371/journal.pone.0195156
|View full text |Cite
|
Sign up to set email alerts
|

Critical in vivo roles of WNT10A in wound healing by regulating collagen expression/synthesis in WNT10A-deficient mice

Abstract: BackgroundWe have reported that WNT10A plays a critical role in the growth of fibroblasts/myofibroblasts and microvascular endothelial cells, i.e.; wound healing/scarring. To ascertain the in vivo regulatory, central functions of WNT10A, we examined the net effects of WNT10A depletion using WNT10A-deficient mice (WNT10A–/–).Methods and resultsWe generated WNT10A–/–mice, displaying a range of unique phenotypes of morpho/organogenetic failure, such as growth retardation, alopecia, kyphosis and infertility, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…WNT10A also plays an important role in cancer. Its absence can delay the healing of dorsal skin wounds in mice [ 57 ], while tumors are considered as “unhealable” wounds. Related to the mechanism of WNT10A in skin wound healing, its absence can inhibit the expression of collagen, thereby preventing tumor occurrence [ 58 ].…”
Section: Discussion and Summarymentioning
confidence: 99%
“…WNT10A also plays an important role in cancer. Its absence can delay the healing of dorsal skin wounds in mice [ 57 ], while tumors are considered as “unhealable” wounds. Related to the mechanism of WNT10A in skin wound healing, its absence can inhibit the expression of collagen, thereby preventing tumor occurrence [ 58 ].…”
Section: Discussion and Summarymentioning
confidence: 99%
“…However, Wnt10a expression was down-regulated in MDSPCs by MRL/MpJ serum. Recently, it was reported that Wnt10 2/2 mice have delayed wound healing in a skin-injury model (33). Next, we asked whether MRL/ MpJ serum has a similar effect on aged MDSPCs.…”
Section: Circulating Serum Factors From Mrl/mpj Mice Regulate Functiomentioning
confidence: 97%
“…This suggests that TGFβ1 serves an activator for fibroblast proliferation and ECM production, whereas TGFβ3 works as an inhibitor of ECM production. Signalling factors belonging to canonical WNT and PDGF pathways also regulate fibroblast activity and can serve the role of activators and inhibitors in the model.…”
Section: Resultsmentioning
confidence: 99%